Débats non formels et engagement des acteurs territoriaux autour du développement de zones arides, fragiles et menacées en Tunisie - Balkis Mzioudet Faillon; Vincent Meyer (Communication)
The authors analyze the questions of trust and communication in the arid, fragile and threatened zone of Menzel Habib, in southeastern Tunisia. Desertification, socio-economic difficulties, the disengagement of the State, and the events of the 2011 Tunisian revolution have amplified the population’s distress. To establish a relationship of trust with the population, to correct a defective information flow and to limit the debilitating effect of a communication blockage, all parties involved must recognize the too long neglected expertise of the local population and its grounded knowledge.